How the active learning method affects students' desire to learn - Agueda Eustaqio; Mauli da Gorráitz; Sarmento Calos Lora (International Journal of Curriculum Development, Teaching and Learning Innovation, 2022)
Researchers found that a mean score of 12.24 was achieved when measuring the level of student enthusiasm to learn while using an active learning strategy. Students whose education follows the traditional model report an average (mean) level of motivation to learn of 11.2. The "t" test's calculations led to the following results: t count = 3.49, and t table = 2.01 for the price. If the number of students taught using an active learning strategy is larger than the number of students taught using a traditional learning approach, then Ho might be rejected. Therefore, this study has successfully demonstrated that the active learning technique, as opposed to the conventional learning approach, increases student learning motivation.